A combined experimental and computational study of novel nanocage-based metal–organic frameworks for drug delivery. Issue 44 (26th October 2015) - Liu, Jian-Qiang; Li, Xue-Feng; Gu, Chu-Ying; da Silva, Júlio C. S.; Barros, Amanda L.; Alves-Jr, Severino; Li, Bao-Hong; Ren, Fei; Batten, Stuart R.; Soares, Thereza A.
Abstract : Experimental and computational characterization of three novel metal organic frameworks (MOFs) with high loading capacity for adsorption and slow release of the drug 5-fluoracil. Abstract : Three new metal organic frameworks (MOFs) with chemical formulae [(CH3 )2 NH2 ] [Sm3 (L1)2 (HCOO)2 (DMF)2 (H2 O)]·2DMF·18H2 O (1 ), [Cu2 (L2)(H2 O)2 ]·2.22DMA (2 ) and [Zn2 (L1)(DMA)]·1.75DMA were synthesized and structurally characterized.1 and2 show a classicalNbO -like topology and have two types of interconnected cages.3 exhibits an uncommonzzz topology and has two types of interconnected cages. These MOFs can adsorb large amounts of the drug 5-fluorouracil (5-FU) and release it in a progressive way. 5-FU was incorporated into desolvated1, 2 and3 with loadings of 0.40, 0.42, and 0.45 g g −1, respectively. The drug release rates were 72%, 96% and 79% of the drug after 96 hours in1, 120 hours in2 and 96 hours in3, respectively. Grand Canonical Monte Carlo (GCMC) simulations were performed to investigate the molecular interactions during 5-FU adsorption to the three novel materials. The GCMC simulations reproduced the experimental trend with respect to the drug loading capacity of each material. They also provided a structural description of drug packing within the frameworks, helping to explain the load capacity and controlled release characteristics of the materials. 5-FU binding preferences to1, 2 and3 reflect the diversity in pore types, chemistry and sizes. The calculated drug load is more related to the molecular properties of accessible volume V acc than to the pore size.